Model of incentive system for employees: A case of a manufacturing company in Croatia - Maria Jakovljevic; Jelena Zupan; Alfred Coleman (South African Journal of Business Management, 2018)
Background: One of the main determinants of a company's business performance is the complete mobility and orientation of its employees towards realising the goals of the company. No single aspect of the company has such a powerful, and simultaneously, invisible influence on the behaviour and feelings of its employees as the organisational climate. Organisational learning creates a climate that encourages employees to learn and to develop their potential.Objectives: The aim of this study is to investigate the incentives and the factors of an organisational climate required to develop a model of an incentive system to motivate employees to work better.Method: A quantitative research methodology was used and data was collected by using a closed-ended type of questionnaire. Data was analysed using descriptive and inferential statistics.Results: The results show that the employees would prefer more incentives, and the factors of a positive organisational climate were far lower than expected by its employees and even lower than what they considered to be essential in order to perform their jobs effectively and to contribute to achieving company objectives.Conclusion: Incentive systems are crucial to employees and the organisational climate and employee satisfaction should be constantly monitored and empowered through an integrated model of incentive system.
Keywords: 650